Characterization and distribution of niosomes containing ursolic acid coated with chitosan layer - Miatmoko, Andang; Safitri, Shofi; Aquila, Fayruz; Cahyani, Devy; Hariawan, Berlian; Hendrianto, Eryk; Hendradi, Esti; Sari, Retno (Research in pharmaceutical sciences, 2021)
Background and purpose: Ursolic acid (UA) exhibits anti-hepatocarcinoma and hepatoprotective activities, thus promising as an effective oral cancer therapy. However, its poor solubility and permeability lead to low oral bioavailability. In this study, we evaluated the effect of different ratios of Span® 60-cholesterol-UA and also chitosan addition on physical characteristics and stability of niosomes to improve oral biodistribution. Experimental approach: UA niosomes (Nio-UA) were composed of Span® 60-cholesterol-UA at different molar ratios and prepared by using thin layer hydration method, and then chitosan solution was added into the Nio-UA to prepare Nio-CS-UA. Findings/Results: The results showed that increasing the UA amount increased the particle size of Nio-UA. However, the higher the UA amount added to niosomes, the lower the encapsulation efficiency. The highest physical stability was achieved by preparing niosomes at a molar ratio of 3:2:10 for Span® 60, cholesterol, and UA, respectively, with a zeta-potential value of -41.99 mV. The addition of chitosan increased the particle size from 255 nm to 439 nm, as well as the zeta-potential value which increased from -46 mV to -21 mV. Moreover, Nio-UA-CS had relatively higher drug release in PBS pH 6.8 and 7.4 than Nio-UA. In the in vivo study, the addition of chitosan produced higher intensities of coumarin-6-labeled Nio-UA-CS in the liver than Nio-UA. Conclusion and implications: It can be concluded that the ratio of Span® 60-cholesterol-UA highly affected niosomes physical properties. Moreover, the addition of chitosan improved the stability and drug release as well as oral biodistribution of Nio-UA.